1997
DOI: 10.1002/(sici)1096-8628(19970627)70:4<361::aid-ajmg6>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Del(10)(q22.3q24.1) associated with juvenile polyposis

Abstract: Juvenile polyps are the most frequent gastrointestinal polyps with a malignant potential for which the genetic basis is unknown. Juvenile polyps, with a normal epithelium but hypertrophic lamina propria, are histologically quite distinct from adenomatous polyps which have dysplastic changes in epithelial nuclei. Furthermore, the adenomatous polyposis coli (APC) gene on Chr 5, mutated somatically in adenomatous polyps and mutated in the germline of patients with familial adenomatous polyposis, is not linked to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…Furthermore, these patients and our double-tg mice both suffer from similar heart septal defects (Delnatte et al, 2006; Jacoby et al, 1997; Menko et al, 2008; Zhou et al, 2001). Thus, facial abnormalities and heart septal defects in human patients might be partly caused by the knockdown of BMPR1A-mediated signaling in NC-derived cells.…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, these patients and our double-tg mice both suffer from similar heart septal defects (Delnatte et al, 2006; Jacoby et al, 1997; Menko et al, 2008; Zhou et al, 2001). Thus, facial abnormalities and heart septal defects in human patients might be partly caused by the knockdown of BMPR1A-mediated signaling in NC-derived cells.…”
Section: Discussionmentioning
confidence: 74%
“…Stromal fibroblasts unresponsive to TGF-b generated HGF and this abnormal paracrine signaling lead to epithelial tumors (Bhowmick et al, 2004;Radisky and Bissell, 2004). Furthermore, stromal defects occur in a number of hereditary gastrointestinal cancers such as juvenile polyposis, where Smad4 and BMP2R mutations account for over 30% of cases (Jacoby et al, 1997;Howe et al, 1998). In these examples, the TGF-b pathway acts as a powerful tumor suppressor, even in the presence of strong oncogene expression (Sternlicht et al, 1999).…”
Section: Capacities For Tissue Contributions Across Germ Layers In Thmentioning
confidence: 99%
“…BmprIa deficiency in CNC lineage also arrested tooth development at the bud/cap stage associated with decreased levels of cell proliferation and down-regulation of several BMP downstream genes in the dental mesenchyme [13]. Interestingly, in a dominant-negative transgenic mouse model, it was shown that reduced BMPRIa-mediated signaling caused facial dysmorphism and cleft palate, mimicking the hypertelorism and flat nasal bridge observed in patients with juvenile polyposis syndrome and chromosome 10q23 deletion syndrome that are associated with BMPRIA mutations or deletion [27], [28], [29], [30], [31]. The indispensable role of BmprIa is further supported by the fact that BmprIb has limited redundant function with BmprIa in tooth and palate development [13].…”
Section: Introductionmentioning
confidence: 96%